Magnetic field associated with an internal fire whirl: A simple model. (February 2018) - Cheng, C.H.; Han, S.S.; Chow, W.K.; Chow, C.L.
Highlights: Measurement of magnetic field due to fire whirl is reported for the first time. Fire whirl is modeled as a rotating plasma and shown to be equivalent to a solenoid. Experimental results agree reasonably well with the solenoid model. Measurement of B field can be used a diagnostic tool for monitoring fire whirl. Limitations and possible extension to more complicated cases are described. Abstract: A fire whirl can be generated by a pool fire in vertical shafts in tall buildings under certain ventilation conditions. Internal fire whirls are much more dangerous and destructive than non-whirling fires in the shaft and deserve more attention. As fires or flames consist of ions in motion, the characteristics of the magnetic field generated by a fire whirl would provide important information. The present study aims at measuring the magnetic field generated by a fire whirl and at building a simple model to explain the generated magnetic field. The physical origin of the magnetic field associated with a fire whirl is proposed, which consists in the interaction of the moving ions with the Earth's magnetic field. It is shown that as far as the magnetic field around a fire whirl is concerned, the fire whirl is equivalent to a solenoid carrying a current Is, which is related to characteristics pertinent to the fire whirl. The vertical component of the magnetic field obtained from this model ( Bzm ) is compared with experimental results ( Bze ) acquired in fire whirls in a shaft model. The two sets of values ( Bzm and Bze ) are well correlated, with deviations which are reasonably acceptable. The results of the present work could be of value as a diagnostic tool in monitoring internal fire whirl and in studying various aspects of the whirl.